Relation between Neutrophil to Lymphocyte Ratio, Platelet to Lymphocyte Ratio and Cerebral Infarct Volume in patients with Ischemic Stroke. - Avni Uygar Seyhan (Albanian Journal of Trauma and Emergency Surgery, 2021)
Abstract :